Properties and applications of Ni-resist and ductile Ni-resist alloys. (Nickel Development Institute, 1998)
There are two families of Ni-Resist austenitic cast irons. These are the standard or flake graphite alloys and the ductile or spheroidal graphite alloys. As time passes, the spheroidal grades, because of higher strength, ductility and elevated temperature properties, are becoming more prominent. However, the flake materials with lower cost, fewer foundry problems and better machinability and thermal conductivity are still produced by many foundries. General characteristics of both groups are described in this publication.